High-temperature-resistant cement and cement paste system for well cementation and preparation method thereof
By optimizing the calcium, silicon, and aluminum ratio in cementing high-temperature resistant cement and using composite blends, the problem of cementite strength decline at high temperature is solved, and stable compressive strength and safe construction in high temperature environments are achieved.
Patent Information
- Application Number
- CN202310708354.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-14
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2043-06-14
AI Technical Summary
In high temperature environments above 200℃, the strength decay problem of conventional silicate cement stone has not been effectively solved, affecting the safety and quality of cementing construction of high-temperature deep wells.
A high-temperature resistant cement system for cementing wells is adopted, including G-grade oil well cement, low-calcium silicate cement, gypsum, sulfur aluminate cement and composite blending materials. The composite blending materials are calcium carbide slag, phosphorus slag, and mussel shells. The mixture of powder and sugar filter sludge is optimized to optimize the calcium, silica, and aluminum ratio to prevent the grains of hydrated products from coarsening, maintain the mesh structure, and improve the high temperature resistance of cement stone.
Within the temperature range of 150℃ to 240℃, the compressive strength of cement stone remains stable without the need for additional reinforcement materials, which reduces engineering costs and ensures the cementing sealing effect and construction safety of high-temperature deep wells.
Smart Images

Figure BDA0004287967760000131
Abstract
Description
Technical Field
[0001] The invention relates to a high temperature resistant cement and cement slurry system for well cementing and a preparation method thereof, and belongs to the field of oil and gas exploration and development. Background Art
[0002] With the deepening of exploration and development, the number of high-temperature and ultra-high-temperature deep wells is increasing, the drilling depth is gradually developing towards 10,000 meters, and the bottom hole circulation temperature is gradually moving towards an ultra-high temperature of 240°C. Under high and ultra-high temperature conditions, the strength decay problem of silicate cement stone is serious, which poses a huge challenge to ensuring the sealing integrity of the cement ring. The commonly adopted measure at present is to select appropriate siliceous admixtures such as quartz sand and mix them with silicate cement. However, the hydration products of sand-added cement change under high temperature conditions above 200°C, and the strength decay phenomenon is obvious, which cannot meet the needs of long-term exploitation of high-temperature oil and gas wells. Therefore, it is necessary to develop a high-temperature resistant cement slurry system to prevent the strength decay of cement stone under high temperature, so as to ensure the safety of cementing construction in high-temperature deep wells and improve the cementing quality.
[0003] CN112094060A discloses a high-temperature cementing cement and its preparation method and application. The cementing cement is composed of 69-72% cement raw materials and 28-31% quartz sand. The cement raw materials are composed of G-grade oil well cement and nuclear power cement in a mass ratio of 4:6-5:5. However, the high-temperature cementing cement is mainly suitable for cementing projects in Africa, and its strength is slightly reduced under the conditions of 130℃-200℃.
[0004] CN101906291A discloses a high-temperature special oil well cement material and a preparation method thereof. The oil well cement material comprises the following components by weight: 100 parts of high belite cement, 10 to 25 parts of quartz sand powder, and 0.22 to 0.32 parts of lignin sulfonate or modified lignin sulfonate or 0.9 to 1.5 parts of ethylenediaminetetramethylenephosphonate. The cement product has the advantages of high thermal stability and low pollution, but is mainly used in oil and gas well repair engineering, has certain limitations in scope of application, and is only applicable to wells with a bottom hole circulation temperature of 60°C to 130°C.
[0005] CN113582605A discloses a high temperature resistant cementing system and its preparation method. The cement system is composed of 25-85 parts by weight of cement, 4-60 parts by weight of silica sand, 4-60 parts by weight of fly ash and additives. The cement system can solve the strength decay problem of cement stone in ultra-high temperature environment, and at the same time solve the land occupation and environmental pollution problems caused by fly ash. Its applicable temperature can reach 200°C. However, after the cement system is cured for 30 days, the compressive strength of the cement stone is less than that of the cement stone cured for 2 days.
[0006] CN115304317A discloses a high temperature strength decay resistant oil well cement slurry system. The cement slurry system is composed of 47.5wt% to 72.5wt% of cementitious material, 15wt% to 25wt% of silica sand, 10wt% to 25wt% of high temperature strength decay resistant material, 2wt% of high temperature stabilizer and 0.5wt% of dispersant. The high temperature strength decay resistant oil well cement slurry system has the advantages of high temperature strength decay resistance and stable high temperature performance, and can effectively alleviate the strength decay problem of cement stone under high temperature conditions.
[0007] CN113683354A discloses an oil well cement slurry system with high temperature strength decay resistance. The oil well cement slurry system comprises the following components by weight: 100.0 parts of oil well cement, 30.0-50.0 parts of quartz sand, 10.0-20.0 parts of high temperature strength decay resistance inhibitor, 3.0-5.0 parts of whisker material, 0.5-2.0 parts of modified carbon nanotubes, 1.0-3.0 parts of dispersant, 2-4 parts of high temperature stabilizer, 1.0-3.0 parts of high temperature fluid loss reducer, 3.0-5.0 parts of high temperature retarder and 65.0-75.0 parts of water. The high temperature strength decay resistance inhibitor comprises two or more of mica, kaolin, wollastonite, chlorite and sepiolite. After curing for 90 days at 240°C, the compressive strength of the cement paste of this cement slurry system is greater than 48MPa. However, high-temperature strength decay inhibitors, modified carbon nanotubes, etc. may shorten the thickening time of the cement slurry to varying degrees, resulting in abnormal setting properties of the cement slurry and affecting the safety of cementing construction.
[0008] At present, most cements used in the field of high temperature recession resistance are aluminate cement, phosphate cement, or ultrafine silicon materials are added to G-grade oil well cement. The strength recession phenomenon at high temperature is weakened, but the problem of cement stone strength recession is not fundamentally solved. When the curing temperature of conventional silicate cement stone is about 110℃, the hydration product will be transformed from amorphous CSH gel to crystalline dicalcium silicate hydrate with poor performance, and the strength recession phenomenon will occur. When the bottom hole circulation temperature is greater than 110℃, the total calcium-silicon ratio of oil well cement can be reduced by adding silica dioxide, so that the cement hydration product can be transformed into relatively good performance tobogostone and xonotlite to maintain stable strength. For many years, the recognized optimal silica sand addition is 30% to 40% of the cement mass. However, recent studies have shown that in a high temperature environment (>150℃), the silicate cement system with silica sand still has obvious microstructure coarsening and strength recession; increasing the silica sand addition (50% to 65%) in a high temperature environment above 200℃ can alleviate the severe strength recession phenomenon, but it still cannot fundamentally solve the problem. In recent years, adding high temperature strength decay resistant materials, such as kaolin and sepiolite, to cement paste can effectively prevent cement paste strength decay under 150-200℃ conditions. However, in engineering applications, high temperature strength decay resistant materials may affect the thickening time of cement paste, making it difficult to ensure cementing construction safety. Therefore, how to ensure the long-term strength stability of cement paste under an environment above 200℃ is still an urgent problem to be solved in cementing engineering.
[0009] Based on these problems, it is of great significance to develop a high-temperature resistant cement for cementing to prevent the strength decline of cement stone under high temperature conditions of 200°C and above. Summary of the invention
[0010] In order to solve the above technical problems, the purpose of the present invention is to provide a high temperature resistant cement and cement slurry system for cementing and a preparation method thereof. The high temperature resistant cement and cement slurry system for cementing provided by the present invention can prevent the strength decline of cement stone under high temperature and ultra-high temperature conditions.
[0011] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a high-temperature resistant cement for cementing, which includes the following components, measured by weight: 40 to 55 parts of G-grade oil well cement, 40 to 55 parts of low-calcium silicate cement, 1 to 5 parts of gypsum, 1 to 10 parts of sulphoaluminate cement, and 1 to 10 parts of composite admixtures; wherein the composite admixture includes a mixture of carbide slag, phosphorus slag, mussel shell powder and sugar filter mud in a weight ratio of 10 to 15: 5 to 10: 3 to 6: 1 to 3.
[0012] In the above-mentioned high temperature resistant cement for cementing, preferably, the weight ratio of G-class oil well cement, low calcium silicate cement, gypsum, sulphoaluminate cement and composite admixture is 40-50:40-50:1-3:5-10:3-6, more preferably 43:43:2:8:4.
[0013] In the above-mentioned high temperature resistant cement for well cementing, preferably, the weight ratio of carbide slag, phosphorus slag, mussel shell powder and sugar filter mud is 10-13:5-8:3-5:1-3.
[0014] In the above-mentioned high temperature resistant cement for cementing, preferably, based on the total weight of the G-grade oil well cement being 100%, the G-grade oil well cement comprises the following components: 95% to 97% of Portland cement clinker and 3% to 5% of gypsum; wherein, based on the total weight of the Portland cement clinker being 100%, the Portland cement clinker comprises the following mineral composition: 40% to 65% of tricalcium silicate, 15% to 25% of dicalcium silicate, 10% to 30% of tricalcium aluminate and tetracalcium aluminoferrite, 1% to 5% of free calcium oxide and free magnesium oxide, and 0% to 0.6% of sodium oxide and potassium oxide.
[0015] In the above-mentioned high temperature resistant cement for cementing, preferably, based on the total weight of the low-calcium silicate cement as 100%, the low-calcium silicate cement includes the following components: 94% to 99% of low-calcium silicate cement clinker and 1% to 6% of gypsum; wherein, based on the total weight of the low-calcium silicate cement clinker as 100%, the low-calcium silicate cement clinker includes the following mineral composition: 45% to 70% of dicalcium silicate, 10% to 40% of tricalcium silicate, 10% to 30% of tricalcium aluminate and tetracalcium aluminoferrite, 1% to 5% of free calcium oxide and free magnesium oxide, and 0% to 0.6% of sodium oxide and potassium oxide.
[0016] In the above-mentioned high temperature resistant cement for cementing, preferably, based on the total weight of the sulphoaluminate cement being 100%, the sulphoaluminate cement comprises the following components: 92% to 95% of sulphoaluminate cement clinker and 5% to 8% of gypsum; wherein, based on the total weight of the sulphoaluminate cement clinker being 100%, the sulphoaluminate cement clinker comprises the following mineral composition: 55% to 75% of calcium sulphoaluminate, 8% to 37% of dicalcium silicate, 15% to 35% of tetracalcium aluminoferrate, 0% to 3% of calcium sulfate, 1% to 5% of free calcium oxide and free magnesium oxide, and 0% to 0.6% of sodium oxide and potassium oxide.
[0017] In the above-mentioned high temperature resistant cement for well cementing, preferably, the gypsum includes one or more combinations of natural dihydrate gypsum, anhydrite (i.e., natural anhydrous gypsum) and mixed gypsum. It should be understood by those skilled in the art that mixed gypsum is a uniform gypsum powder with a gelling effect prepared by fully mixing, calcining, grinding and other processes any two or more gypsum raw materials (such as natural dihydrate gypsum, anhydrite or various industrial by-product gypsum). The present invention does not limit the specific composition of the mixed gypsum, which can be obtained commercially. The gypsum refers to the gypsum in the components of the high temperature resistant cement for well cementing, the gypsum in the components of the G-grade oil well cement, the gypsum in the components of the low calcium silicate cement, and the gypsum in the components of the sulphoaluminate cement.
[0018] In the above-mentioned high temperature resistant cement for well cementing, preferably, the mass content of Ca(OH)2 in the carbide slag is 70% to 80%.
[0019] In the above-mentioned high temperature resistant cement for well cementing, preferably, the particle size of the carbide slag is 10 to 15 μm.
[0020] In the above-mentioned high temperature resistant cement for cementing, preferably, the mass content of P2O5 in the phosphorus slag is 40% to 43%, the mass content of SiO2 is 47% to 52%, the mass content of Fe2O3 is 2% to 5%, the mass content of fluoride is 0.8% to 3%, and the mass content of Al2O3 is 0.8% to 2.5%.
[0021] In the above-mentioned high temperature resistant cement for well cementing, preferably, the particle size of the phosphorus slag is 0.5 to 5 mm.
[0022] In the above-mentioned high temperature resistant cement for well cementing, preferably, the content of CaCO3 in the mussel shell powder is 90% to 96%.
[0023] In the above-mentioned high temperature resistant cement for well cementing, preferably, the particle size of the mussel shell powder is 200-300 μm.
[0024] In the above-mentioned high temperature resistant cement for well cementing, preferably, the mass content of CaCO3 in the sugar filter mud is 55% to 70%.
[0025] According to a specific embodiment of the present invention, the high temperature resistant cement for cementing is prepared by the following steps: G-grade oil well cement, low calcium silicate cement, gypsum, sulphoaluminate cement and composite admixtures are uniformly mixed according to the above-mentioned weight portions to obtain the high temperature resistant cement for cementing.
[0026] The second aspect of the present invention provides a high temperature resistant cement slurry system for cementing, which includes the following components, in parts by weight: 100 parts of the above-mentioned high temperature resistant cement for cementing, 0 to 70 parts of quartz sand, 1 to 6 parts of a suspension stabilizer, 2 to 9 parts of a fluid loss reducer, 0.5 to 1.5 parts of a dispersant, 1 to 9 parts of a retarder, 0.1 to 0.5 parts of a defoaming agent, and 40 to 100 parts of water.
[0027] In the above-mentioned high temperature resistant cement slurry system for cementing, preferably, the particle size of the quartz sand is 50 mesh to 5000 mesh. According to a specific embodiment of the present invention, the quartz sand includes ordinary quartz sand and / or acid washed quartz sand.
[0028] In the above-mentioned high temperature resistant cement slurry system for cementing, the suspension stabilizer can be a conventional suspension stabilizer for oil well cement in the art, such as an acrylamide polymer suspension stabilizer, etc. Preferably, the suspension stabilizer includes a polymer suspension stabilizer prepared from 2-acrylamido-2-methylpropanesulfonic acid, acrylamide, diallyldimethylammonium chloride and N-vinylpyrrolidone as monomers. The polymer suspension stabilizer can be prepared by referring to the steps disclosed in CN113736016A.
[0029] In the above-mentioned high temperature resistant cement slurry system for cementing, the fluid loss reducer can be a conventional fluid loss reducer for oil well cement in the art, such as 2-acrylamide-2-methylpropanesulfonic acid polymer fluid loss reducer. Preferably, the fluid loss reducer includes a polymer fluid loss reducer prepared from 2-acrylamide-2-methylpropanesulfonic acid, N,N-dimethylacrylamide and unsaturated carboxylic acid as monomers. Among them, the unsaturated carboxylic acid can be acrylic acid or itaconic acid. The polymer fluid loss reducer can be prepared by referring to, but not limited to, the steps disclosed in the synthesis and performance evaluation of salt-resistant fluid loss reducer AMPS / DMAA / IA (Yu Wenjuan et al., Chemical Industry and Engineering, 2018, 35(1):6).
[0030] In the above-mentioned high temperature resistant cement slurry system for cementing, the dispersant can be a conventional dispersant for oil well cement in the art. Preferably, the dispersant includes an aldehyde ketone condensation polymer dispersant and / or a polycarboxylic acid dispersant.
[0031] In the above-mentioned high temperature resistant cement slurry system for cementing, the retarder can be a conventional retarder for oil well cement in the art. Preferably, the retarder includes one or a combination of hydroxyethylidene diphosphonic acid (HEDP), ethylenediaminetetramethylenephosphonic acid (EDTMPA) and ethylenediaminetetramethylenephosphonate.
[0032] In the above-mentioned high temperature resistant cement slurry system for cementing, the defoamer can be a conventional defoamer for oil well cement in the art. Preferably, the defoamer includes one or a combination of tributyl phosphate, polyoxypropylene glycerol ether and polydimethylsiloxane.
[0033] According to a specific embodiment of the present invention, the above-mentioned high temperature resistant cement slurry system for cementing is prepared by dry mixing and wet mixing the components according to the dry and wet states, and then mixing the dry mixture with the wet mixture. Preferably, the above-mentioned high temperature resistant cement slurry system for cementing is prepared by the following steps: high temperature resistant cement for cementing, quartz sand, suspension stabilizer, and dispersant are uniformly mixed according to the above-mentioned weight portions to obtain a dry mixture; fluid loss reducer, retarder, defoamer, and water are uniformly mixed according to the above-mentioned weight portions to obtain a wet mixture; at a speed of 4000±200r / min, the dry mixture is evenly poured into the wet mixture, and after the dry mixture is completely added to the wet mixture, the speed is adjusted to 12000±500r / min, and stirring is continued for 15 to 35s to obtain the high temperature resistant cement slurry system for cementing.
[0034] The third aspect of the present invention provides a method for preparing the above-mentioned high temperature resistant cement slurry system for cementing, which comprises the following steps:
[0035] The high temperature resistant cement for cementing, quartz sand, suspension stabilizer and dispersant are mixed uniformly according to weight parts to obtain a dry mix; the fluid loss reducer, retarder, defoamer and water are mixed uniformly according to weight parts to obtain a wet mix; at a rotation speed of 4000±200r / min, the dry mix is evenly poured into the wet mix, and after the dry mix is completely added to the wet mix, the rotation speed is adjusted to 12000±500r / min, and stirring is continued for 15-35s to obtain the high temperature resistant cement slurry system for cementing.
[0036] The technical solution of the present invention has at least the following beneficial effects:
[0037] (1) Under ultra-high temperature conditions of 240°C, as the high-temperature curing age increases, the network structure of needle-shaped xonotlite grains in the hydration product disappears, the tightness between crystals decreases significantly, and the xonotlite grains coarsen, resulting in a serious reduction in the high-temperature mechanical properties of sand-added oil well cement. The present invention optimizes the calcium-silicon-aluminum ratio of cement by compounding G-grade oil well cement, low-calcium silicate cement, sulphoaluminate cement, gypsum and composite admixtures, thereby optimizing the hydration product components and effectively improving the mechanical properties of cement at high temperatures. The present invention uses a composite admixture, which is a mixture of carbide slag, phosphorus slag, mussel shell powder and sugar filter mud in a weight ratio of 10 to 15:5 to 10:3 to 6:1 to 3. The composite admixture designed by the present invention can effectively improve the high-temperature strength decline resistance of cement. The design of the cement formula of the present invention can prevent the grain coarsening of the hydration product and maintain a mesh structure of interlaced and overlapped grains. The dense structure formed by the xonotlite in the main hydration product plays a key role in improving the mechanical properties of high-temperature cement paste.
[0038] (2) Conventional G-class oil well cement sand-adding systems must add reinforcing materials and anti-strength decay materials to achieve the effect of no decay of cement stone strength under high temperature conditions. However, there are many types of reinforcing materials and anti-strength decay materials and they are expensive. Special cements such as phosphates and aluminates require special admixtures. The research and development costs of these special admixtures are high and their economic efficiency is poor. The high-temperature resistant cement components for cementing of the present invention include G-class oil well cement, low-calcium silicate cement, gypsum, sulfoaluminate cement and composite admixtures; the composite admixtures include a mixture of carbide slag, phosphorus slag, mussel shell powder and sugar filter mud in a weight ratio of 10 to 15:5 to 10:3 to 6:1 to 3. The raw materials used in the present invention are cement, gypsum and solid waste, which are low in price and effectively save engineering costs.
[0039] (3) The high temperature resistant cement for cementing provided by the present invention is used only with quartz sand and basic admixtures matching silicate cement to form a high temperature resistant cement slurry system for cementing. The high temperature resistant cement slurry system for cementing of the present invention has an adjustable thickening time, and does not require external reinforcement materials, strength decay prevention materials, etc., thereby avoiding the occurrence of problems such as excessive external admixtures in the cement slurry system leading to unadjustable thickening time, slurry thickening, and thus affecting cementing construction safety.
[0040] In summary, the present invention provides a high-temperature resistant cement and cement slurry system for cementing and a preparation method thereof. The applicable bottom hole circulation temperature range of the cement and cement slurry system of the present invention is 150°C to 240°C. The compressive strength of the cement stone cured for 28 days in this temperature range is greater than 40MPa, and there is no decline in the compressive strength of the cement stone cured for 2 days, which solves the problem that the strength decline of cement stone above 200°C affects high-quality exploration and development. At the same time, the high-temperature resistant cement slurry system for cementing of the present invention has a suitable thickening time, and there is no problem of abnormal setting performance of cement slurry due to too short thickening time. The high-temperature resistant cement and cement slurry system for cementing provided by the present invention ensures the cementing sealing effect and cementing construction safety under high-temperature, ultra-high-temperature deep wells and ultra-deep wells, and improves the cementing quality. DETAILED DESCRIPTION
[0041] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.
[0042] In the following examples and comparative examples, the raw materials used include G-class oil well cement (high sulfate resistance type), low calcium silicate cement, anhydrite, natural dihydrate gypsum, sulphoaluminate cement, carbide slag, phosphorus slag, mussel shell powder, sugar filter mud, quartz sand, suspension stabilizer, retarder, fluid loss agent, dispersant and defoamer, etc., all of which are commercially available. The water used is distilled water.
[0043] Among them, based on the total weight of G-grade oil well cement as 100%, its components are: 96% of silicate cement clinker and 4% of gypsum; based on the total weight of silicate cement clinker as 100%, its mineral composition is: 54% of tricalcium silicate, 23% of dicalcium silicate, 2% of tricalcium aluminate, 17% of tetracalcium aluminoferrite, 1.7% of free calcium oxide, 2% of free magnesium oxide, 0.1% of sodium oxide and 0.2% of potassium oxide.
[0044] Based on the total weight of low-calcium silicate cement being 100%, its components are: 97% of low-calcium silicate cement clinker and 3% of gypsum; based on the total weight of low-calcium silicate cement clinker being 100%, its mineral composition is: 49% of dicalcium silicate, 29% of tricalcium silicate, 2% of tricalcium aluminate, 16% of tetracalcium aluminoferrite, 2.1% of free calcium oxide, 1.6% of free magnesium oxide, 0.1% of sodium oxide and 0.2% of potassium oxide.
[0045] Based on the total weight of sulphoaluminate cement being 100%, its components are: 94% of sulphoaluminate cement clinker and 6% of gypsum; based on the total weight of sulphoaluminate cement clinker being 100%, its mineral composition is: 64% of calcium sulphoaluminate, 16% of dicalcium silicate, 15% of tetracalcium aluminoferrate, 2.1% of free calcium oxide, 2.7% of free magnesium oxide, 0.1% of sodium oxide and 0.1% of potassium oxide.
[0046] The gypsum in the components of G-grade oil well cement, the gypsum in the components of low-calcium silicate cement, and the gypsum in the components of sulphoaluminate cement are all mixtures of anhydrite and natural dihydrate gypsum in a mass ratio of 1:1.
[0047] The mass content of Ca(OH)2 in the carbide slag is 70% to 80%. The particle size of the carbide slag is 10 to 15 μm.
[0048] The mass content of P2O5 in the phosphorus slag is 40% to 43%, the mass content of SiO2 is 47% to 52%, the mass content of Fe2O3 is 2% to 5%, the mass content of fluoride is 0.8% to 3%, and the mass content of Al2O3 is 0.8% to 2.5%. The particle size of the phosphorus slag is 0.5 to 5 mm.
[0049] The content of CaCO3 in the mussel shell powder is 90% to 96%. The particle size of the mussel shell powder is 200 to 300 μm.
[0050] The mass content of CaCO3 in sugar filter mud is 55% to 70%.
[0051] The suspension stabilizer is a product of China National Petroleum Corporation Engineering Technology Research Institute Co., Ltd., model DRK-3S.
[0052] The retarder is a product of China National Petroleum Corporation Engineering Technology Research Institute Co., Ltd., model DRH-3L.
[0053] The fluid loss additive is a product of China National Petroleum Corporation Engineering Technology Research Institute Co., Ltd., model DRF-3L.
[0054] The dispersant is a product of China National Petroleum Corporation Engineering Technology Research Institute Co., Ltd., model DRS-2S.
[0055] The defoaming agent is a product of China National Petroleum Corporation Engineering Technology Research Institute Co., Ltd., model DRX-1L.
[0056] Example 1
[0057] This embodiment provides a high temperature resistant cement for cementing, which includes the following components by weight: 43 parts of G-grade oil well cement, 43 parts of low calcium silicate cement, 2 parts of gypsum, 8 parts of sulphoaluminate cement, and 4 parts of composite admixture; wherein the composite admixture is a mixture of carbide slag, phosphorus slag, mussel shell powder and sugar filter mud in a weight ratio of 10:5:3:1. wherein the gypsum is a mixture of anhydrite and natural dihydrate gypsum in a mass ratio of 1:1.
[0058] This embodiment also provides a high temperature resistant cement slurry system for cementing, which includes the following components by weight: 100 parts of the high temperature resistant cement for cementing of this embodiment, 30 parts of 200 mesh ordinary quartz sand, 20 parts of 1500 mesh ordinary quartz sand, 3 parts of suspension stabilizer, 4 parts of fluid loss reducer, 1.2 parts of dispersant, 3 parts of retarder, 0.2 parts of defoamer and 51 parts of water. The density of the high temperature resistant cement slurry system for cementing is 1.90g / cm 3 .
[0059] The high temperature resistant cement slurry system for cementing in this embodiment is prepared by the following steps: mixing the high temperature resistant cement for cementing, quartz sand, suspension stabilizer and dispersant in the above-mentioned weight portions to obtain a dry mix; mixing the fluid loss reducer, retarder, defoamer and water in the above-mentioned weight portions to obtain a wet mix; using a mixer, at a speed of 4000±200r / min, evenly pouring the dry mix into the wet mix, after the dry mix is completely added to the wet mix, covering the mixer with a lid, adjusting the speed to 12000±500r / min, and continuing to stir for 35s to obtain the high temperature resistant cement slurry system for cementing.
[0060] Example 2
[0061] This embodiment provides a high temperature resistant cement slurry system for cementing, which includes the following components in parts by weight: 100 parts of the high temperature resistant cement for cementing provided in Example 1, 30 parts of 200 mesh ordinary quartz sand, 20 parts of 1500 mesh ordinary quartz sand, 4 parts of suspension stabilizer, 5 parts of fluid loss reducer, 1.2 parts of dispersant, 5 parts of retarder, 0.2 parts of defoamer and 49 parts of water. The density of the high temperature resistant cement slurry system for cementing is 1.90 g / cm 3 The preparation steps of the high temperature resistant cement slurry system for cementing are the same as those in Example 1.
[0062] Example 3
[0063] This embodiment provides a high temperature resistant cement slurry system for cementing, which includes the following components in parts by weight: 100 parts of the high temperature resistant cement for cementing provided in Example 1, 4 parts of a suspension stabilizer, 3 parts of a fluid loss reducer, 1 part of a dispersant, 2 parts of a retarder, 0.2 parts of a defoamer, and 39 parts of water. The density of the high temperature resistant cement slurry system for cementing is 1.90 g / cm3 The preparation steps of the high temperature resistant cement slurry system for cementing are the same as those in Example 1.
[0064] Example 4
[0065] This embodiment provides a high temperature resistant cement for cementing, which includes the following components by weight: 55 parts of G-grade oil well cement, 40 parts of low calcium silicate cement, 1 part of gypsum, 2 parts of sulphoaluminate cement, and 2 parts of composite admixture; wherein the composite admixture is a mixture of carbide slag, phosphorus slag, mussel shell powder and sugar filter mud in a weight ratio of 10:5:3:1. wherein the gypsum is a mixture of anhydrite and natural dihydrate gypsum in a mass ratio of 1:1.
[0066] This embodiment also provides a high temperature resistant cement slurry system for cementing, which includes the following components by weight: 100 parts of the high temperature resistant cement for cementing of this embodiment, 30 parts of 200 mesh ordinary quartz sand, 20 parts of 1500 mesh ordinary quartz sand, 3 parts of suspension stabilizer, 4 parts of fluid loss reducer, 1.2 parts of dispersant, 3 parts of retarder, 0.2 parts of defoamer and 51 parts of water. The density of the high temperature resistant cement slurry system for cementing is 1.90g / cm 3 .
[0067] Example 5
[0068] This embodiment provides a high temperature resistant cement for cementing, which includes the following components by weight: 40 parts of G-grade oil well cement, 55 parts of low calcium silicate cement, 1 part of gypsum, 2 parts of sulphoaluminate cement, and 2 parts of composite admixture; wherein the composite admixture is a mixture of carbide slag, phosphorus slag, mussel shell powder and sugar filter mud in a weight ratio of 10:5:3:1. wherein the gypsum is a mixture of anhydrite and natural dihydrate gypsum in a mass ratio of 1:1.
[0069] This embodiment also provides a high temperature resistant cement slurry system for cementing, which includes the following components by weight: 100 parts of the high temperature resistant cement for cementing of this embodiment, 30 parts of 200 mesh ordinary quartz sand, 20 parts of 1500 mesh ordinary quartz sand, 3 parts of suspension stabilizer, 4 parts of fluid loss reducer, 1.2 parts of dispersant, 3 parts of retarder, 0.2 parts of defoamer and 51 parts of water. The density of the high temperature resistant cement slurry system for cementing is 1.90g / cm 3 .
[0070] Example 6
[0071] This embodiment provides a high temperature resistant cement for cementing, which includes the following components by weight: 40 parts of G-grade oil well cement, 40 parts of low calcium silicate cement, 5 parts of gypsum, 5 parts of sulphoaluminate cement, and 10 parts of composite admixture; wherein the composite admixture is a mixture of carbide slag, phosphorus slag, mussel shell powder and sugar filter mud in a weight ratio of 10:5:3:1. wherein the gypsum is a mixture of anhydrite and natural dihydrate gypsum in a mass ratio of 1:1.
[0072] This embodiment also provides a high temperature resistant cement slurry system for cementing, which includes the following components by weight: 100 parts of the high temperature resistant cement for cementing of this embodiment, 30 parts of 200 mesh ordinary quartz sand, 20 parts of 1500 mesh ordinary quartz sand, 3 parts of suspension stabilizer, 4 parts of fluid loss reducer, 1.2 parts of dispersant, 3 parts of retarder, 0.2 parts of defoamer and 51 parts of water. The density of the high temperature resistant cement slurry system for cementing is 1.90g / cm 3 .
[0073] Example 7
[0074] This embodiment provides a high temperature resistant cement for cementing, which includes the following components by weight: 40 parts of G-grade oil well cement, 40 parts of low calcium silicate cement, 5 parts of gypsum, 5 parts of sulphoaluminate cement, and 10 parts of composite admixture; wherein the composite admixture is a mixture of carbide slag, phosphorus slag, mussel shell powder and sugar filter mud in a weight ratio of 15:10:6:3. wherein the gypsum is a mixture of anhydrite and natural dihydrate gypsum in a mass ratio of 1:1.
[0075] This embodiment also provides a high temperature resistant cement slurry system for cementing, which includes the following components by weight: 100 parts of the high temperature resistant cement for cementing of this embodiment, 30 parts of 200 mesh ordinary quartz sand, 20 parts of 1500 mesh ordinary quartz sand, 3 parts of suspension stabilizer, 4 parts of fluid loss reducer, 1.2 parts of dispersant, 3 parts of retarder, 0.2 parts of defoamer and 51 parts of water. The density of the high temperature resistant cement slurry system for cementing is 1.90g / cm 3 .
[0076] Comparative Example 1
[0077] This comparative example provides a cement slurry system for cementing, which includes the following components by weight: 100 parts of G-grade oil well cement, 30 parts of 200-mesh ordinary quartz sand, 20 parts of 1500-mesh ordinary quartz sand, 3 parts of suspension stabilizer, 4 parts of fluid loss reducer, 1.2 parts of dispersant, 3 parts of retarder, 0.2 parts of defoamer and 51 parts of water. The density of the cement slurry system for cementing is 1.90 g / cm 3 The preparation steps of the cement slurry system for cementing are the same as those in Example 1.
[0078] Comparative Example 2
[0079] This comparative example provides a cement slurry system for cementing, which includes the following components by weight: 100 parts of G-grade oil well cement, 30 parts of 200-mesh ordinary quartz sand, 20 parts of 1500-mesh ordinary quartz sand, 4 parts of suspension stabilizer, 5 parts of fluid loss reducer, 1.2 parts of dispersant, 5 parts of retarder, 0.2 parts of defoamer and 49 parts of water. The density of the cement slurry system for cementing is 1.90 g / cm 3 The preparation steps of the cement slurry system for cementing are the same as those in Example 1.
[0080] Comparative Example 3
[0081] This comparative example provides a cement for cementing, which includes the following components in parts by weight: 34 parts of G-grade oil well cement, 52 parts of low-calcium silicate cement, 4 parts of gypsum, 6 parts of sulphoaluminate cement, and 4 parts of composite admixture; wherein the composite admixture is a mixture of carbide slag, phosphorus slag, mussel shell powder, and sugar filter mud in a weight ratio of 10:5:3:1. wherein the gypsum is a mixture of anhydrite and natural dihydrate gypsum in a mass ratio of 1:1.
[0082] The comparative example also provides a cement slurry system for cementing, which includes the following components by weight: 100 parts of cement for cementing of the comparative example, 30 parts of 200 mesh ordinary quartz sand, 20 parts of 1500 mesh ordinary quartz sand, 4 parts of suspension stabilizer, 5 parts of fluid loss reducer, 1.2 parts of dispersant, 5 parts of retarder, 0.2 parts of defoamer and 49 parts of water. The density of the cement slurry system for cementing is 1.90 g / cm 3 The preparation steps of the cement slurry system for cementing are the same as those in Example 1.
[0083] Comparative Example 4
[0084] This comparative example provides a cement for cementing, which includes the following components by weight: 52 parts of G-grade oil well cement, 34 parts of low-calcium silicate cement, 5 parts of gypsum, 5 parts of sulphoaluminate cement, and 4 parts of composite admixture; wherein the composite admixture is a mixture of carbide slag, phosphorus slag, mussel shell powder, and sugar filter mud in a weight ratio of 10:5:3:1. wherein the gypsum is a mixture of anhydrite and natural dihydrate gypsum in a mass ratio of 1:1.
[0085] The comparative example also provides a cement slurry system for cementing, which includes the following components by weight: 100 parts of cement for cementing of the comparative example, 30 parts of 200 mesh ordinary quartz sand, 20 parts of 1500 mesh ordinary quartz sand, 4 parts of suspension stabilizer, 5 parts of fluid loss reducer, 1.2 parts of dispersant, 5 parts of retarder, 0.2 parts of defoamer and 49 parts of water. The density of the cement slurry system for cementing is 1.90 g / cm 3The preparation steps of the cement slurry system for cementing are the same as those in Example 1.
[0086] Comparative Example 5
[0087] This comparative example provides a cement for cementing, which includes the following components in parts by weight: 43 parts of G-grade oil well cement, 43 parts of low-calcium silicate cement, 2 parts of gypsum, 8 parts of sulphoaluminate cement, and 4 parts of composite admixture; wherein the composite admixture is a mixture of carbide slag, phosphorus slag and mussel shell powder in a weight ratio of 20:4:2. wherein the gypsum is a mixture of anhydrite and natural dihydrate gypsum in a mass ratio of 1:1.
[0088] The comparative example also provides a cement slurry system for cementing, which includes the following components by weight: 100 parts of cement for cementing of the comparative example, 30 parts of 200 mesh ordinary quartz sand, 20 parts of 1500 mesh ordinary quartz sand, 3 parts of suspension stabilizer, 4 parts of fluid loss reducer, 1.2 parts of dispersant, 3 parts of retarder, 0.2 parts of defoamer and 51 parts of water. The density of the cement slurry system for cementing is 1.90 g / cm 3 The preparation steps of the cement slurry system for cementing are the same as those in Example 1.
[0089] Comparative Example 6
[0090] This comparative example provides a cement for cementing, which includes the following components in parts by weight: 45 parts of G-grade oil well cement, 45 parts of low-calcium silicate cement, 2 parts of gypsum, and 8 parts of sulphoaluminate cement. The gypsum is a mixture of anhydrite and natural dihydrate gypsum in a mass ratio of 1:1.
[0091] The comparative example also provides a cement slurry system for cementing, which includes the following components by weight: 100 parts of cement for cementing of the comparative example, 30 parts of 200 mesh ordinary quartz sand, 20 parts of 1500 mesh ordinary quartz sand, 3 parts of suspension stabilizer, 4 parts of fluid loss reducer, 1.2 parts of dispersant, 3 parts of retarder, 0.2 parts of defoamer and 51 parts of water. The density of the cement slurry system for cementing is 1.90 g / cm 3 The preparation steps of the cement slurry system for cementing are the same as those in Example 1.
[0092] Comparative Example 7
[0093] This comparative example provides a cement slurry system for cementing, which includes the following components in parts by weight: 100 parts of cement for cementing provided in comparative example 6, 30 parts of 200 mesh ordinary quartz sand, 20 parts of 1500 mesh ordinary quartz sand, 4 parts of suspension stabilizer, 5 parts of fluid loss reducer, 1.2 parts of dispersant, 5 parts of retarder, 0.2 parts of defoamer and 49 parts of water. The density of the cement slurry system for cementing is 1.90 g / cm 3The preparation steps of the cement slurry system for cementing are the same as those in Example 1.
[0094] Test Case
[0095] The thickening time and compressive strength of cement paste of the cement slurry systems provided in the above-mentioned Examples 1 to 7 and Comparative Examples 1 to 7 were tested according to the standard GB / T 19139-2012 "Test Methods for Oil Well Cement". The main experimental instruments in the test process include: 30-60 type rib mixer (CHANDLER Company, USA), 8240 type high temperature and high pressure thickener (CHANDLER Company, USA), and ultra-high temperature curing kettle (Shenyang Tiger Petroleum Instrument Equipment Manufacturing Co., Ltd.). The test results are shown in Table 1.
[0096] Table 1
[0097]
[0098] It can be seen from Table 1 that under 200°C, the compressive strength of the cement stone of the ordinary G-grade oil well cement and sand cement slurry system provided in Comparative Example 1 after curing for 28 days is seriously degraded compared with the compressive strength of the cement stone cured for 2 days. By comparing Example 1 and Comparative Example 1, it can be seen that when the difference in thickening time is not large, the strength of the cement stone of the high temperature resistant cement slurry system for cementing in Example 1 is 45.8MPa after curing for 2 days, and the strength of the cement stone is 53.8MPa after curing for 28 days, which proves that the strength of the cement slurry system in Example 1 does not decline under high temperature conditions of 200°C, and the 2-day and 28-day compressive strengths of the cement stone are both higher than those of the G-grade oil well cement and sand cement slurry system in Comparative Example 1. In addition, the thickening time of the cement slurry system in Example 1 is adjustable, the thickening curve is normal, and it can meet the engineering performance requirements.
[0099] Under the condition of 240°C, the compressive strength of the cement stone of the ordinary G-grade oil well cement and sand cement slurry system provided in Comparative Example 2 after curing for 28 days seriously declines compared with the compressive strength of the cement stone after curing for 2 days. By comparing Example 2 and Comparative Example 2, it can be seen that when the difference in thickening time is not large, the strength of the cement stone of the high temperature resistant cement slurry system for cementing in Example 2 is 48.4MPa after curing for 2 days, and the strength of the cement stone is 56.1MPa after curing for 28 days, which proves that the strength of the cement slurry system in Example 2 does not decline under the ultra-high temperature condition of 240°C, and the 2-day and 28-day compressive strengths of the cement stone are both higher than those of the G-grade oil well cement and sand cement slurry system provided in Comparative Example 2.
[0100] Under the condition of 150°C, the compressive strength of the cement paste cured for 28 days by the high temperature resistant cement slurry system for cementing without adding sand provided in Example 3 is still greater than 40 MPa, and there is no decline in the compressive strength of the cement paste compared with the compressive strength of the cement paste cured for 2 days.
[0101] The weight ratios of G-class oil well cement, low calcium silicate cement, gypsum, sulphoaluminate cement and composite admixtures in the cement used for cementing in Example 2, Comparative Example 3 and Comparative Example 4 are 43:43:2:8:4, 34:52:4:6:4 and 52:34:5:5:4 respectively. Under the condition of 240°C, the cement prepared by Example 2 using G-class oil well cement, low calcium silicate cement, gypsum, sulphoaluminate cement and composite admixtures in a weight ratio of 43:43:2:8:4 has the highest compressive strength of cement paste. However, the weight ratios of the components in the cement formulas of Comparative Examples 3 and 4 are not within the scope of the present invention, and the compressive strength of cement paste is low. The 28-day compressive strength of the cement paste of Example 2 and Comparative Examples 3 and 4 is not degraded compared with the 2-day compressive strength. It can be seen that the cement for cementing made of G-class oil well cement, low calcium silicate cement, gypsum, sulphoaluminate cement, and composite admixtures helps to improve the mechanical properties of cement stone under high temperature conditions and prevent the high temperature strength of cement stone from declining. However, the mixing ratio of the components in the cement of the present invention has the most significant effect on improving the mechanical properties of cement stone. In addition, the optimal weight ratio of G-class oil well cement, low calcium silicate cement, gypsum, sulphoaluminate cement, and composite admixtures in the high temperature resistant cement for cementing of the present invention is 43:43:2:8:4.
[0102] The composite admixture in the high temperature resistant cement for cementing of Example 1 is a mixture of carbide slag, phosphorus slag, mussel shell powder and sugar filter mud in a weight ratio of 10:5:3:1. The composite admixture in the cement for cementing of Comparative Example 5 is a mixture of carbide slag, phosphorus slag and mussel shell powder in a weight ratio of 20:4:2. The cement for cementing of Comparative Example 6 does not use composite admixtures. Under the condition of 200°C, the compressive strength of the cement paste of Example 1 is the highest, while the compressive strength of the cement paste of Comparative Example 6 is the lowest; and the 28-day compressive strength of the cement paste of Example 1 and Comparative Examples 5 and 6 is not degraded compared with the 2-day compressive strength. The high temperature resistant cement slurry system for cementing of Examples 4 to 7 has no strength degradation under high temperature conditions of 200°C; and the 28-day compressive strength of the cement paste of Examples 4 to 7 is higher than that of Comparative Examples 5 and 6.
[0103] The composite admixture in the high temperature resistant cement for cementing of Example 2 is a mixture of carbide slag, phosphorus slag, mussel shell powder and sugar filter mud in a weight ratio of 10:5:3:1. The cement for cementing of Comparative Example 7 does not use the composite admixture. Under the condition of 240°C, the compressive strength of the cement paste of Example 2 is significantly higher than that of Comparative Example 7.
[0104] It can be seen that the use of the weight ratio of the present invention to compound G-grade oil well cement, low-calcium silicate cement, gypsum, and sulphoaluminate cement can achieve a certain effect of preventing the high-temperature strength decline of cement paste. The composite admixture designed by the present invention has a significant effect on improving the mechanical properties of cement paste.
[0105] In summary, the high temperature resistant cement and cement slurry system for cementing provided by the present invention is applicable to the bottom hole circulation temperature range of 150℃~240℃, and the compressive strength of the cement stone cured for 28 days in this temperature range is greater than 40MPa (the compressive strength of the cement stone cured for 28 days by the sand-added cement slurry system is greater than 50MPa), and there is no decline in the compressive strength of the cement stone cured for 2 days, which solves the problem that the strength decline of cement stone above 200℃ affects high-quality exploration and development. At the same time, the high temperature resistant cement slurry system for cementing provided by the present invention has a suitable thickening time, and the thickening time is adjustable, and there is no problem of abnormal setting performance of cement slurry due to too short thickening time. The high temperature resistant cement and cement slurry system for cementing provided by the present invention ensures the cementing sealing effect and cementing construction safety under high temperature, ultra-high temperature deep well and ultra-deep well conditions, and improves the cementing quality.
[0106] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.
Claims
1. A high temperature resistant cement for cementing, comprising the following components, by weight: 40-55 parts of G-grade oil well cement, 40-55 parts of low calcium silicate cement, 1-5 parts of gypsum, 1-10 parts of sulphoaluminate cement, and 1-10 parts of composite admixture; wherein: The composite admixture comprises a mixture of carbide slag, phosphorus slag, mussel shell powder and sugar filter mud in a weight ratio of 10-15:5-10:3-6:1-3.
2. The high temperature resistant cement for cementing according to claim 1, wherein: Taking the total weight of the G-grade oil well cement as 100%, the G-grade oil well cement includes the following components: 95% to 97% of silicate cement clinker and 3% to 5% of gypsum; wherein, taking the total weight of the silicate cement clinker as 100%, the silicate cement clinker includes the following mineral composition: 40% to 65% of tricalcium silicate, 15% to 25% of dicalcium silicate, 10% to 30% of tricalcium aluminate and tetracalcium aluminoferrite, 1% to 5% of free calcium oxide and free magnesium oxide, and 0% to 0.6% of sodium oxide and potassium oxide.
3. The high temperature resistant cement for cementing according to claim 1, wherein: Taking the total weight of the low-calcium silicate cement as 100%, the low-calcium silicate cement includes the following components: 94% to 99% of low-calcium silicate cement clinker and 1% to 6% of gypsum; wherein, taking the total weight of the low-calcium silicate cement clinker as 100%, the low-calcium silicate cement clinker includes the following mineral composition: 45% to 70% of dicalcium silicate, 10% to 40% of tricalcium silicate, 10% to 30% of tricalcium aluminate and tetracalcium aluminoferrite, 1% to 5% of free calcium oxide and free magnesium oxide, and 0% to 0.6% of sodium oxide and potassium oxide.
4. The high temperature resistant cement for cementing according to claim 1, wherein: Taking the total weight of the sulphoaluminate cement as 100%, the sulphoaluminate cement includes the following components: 92% to 95% of sulphoaluminate cement clinker and 5% to 8% of gypsum; wherein, taking the total weight of the sulphoaluminate cement clinker as 100%, the sulphoaluminate cement clinker includes the following mineral composition: 55% to 75% of calcium sulphoaluminate, 8% to 37% of dicalcium silicate, 15% to 35% of tetracalcium aluminoferrate, 0% to 3% of calcium sulfate, 1% to 5% of free calcium oxide and free magnesium oxide, and 0% to 0.6% of sodium oxide and potassium oxide.
5. The high temperature resistant cement for cementing according to any one of claims 1 to 4, wherein: The gypsum includes one or a combination of natural dihydrate gypsum, anhydrite and mixed gypsum.
6. The high temperature resistant cement for cementing according to claim 1, wherein: The mass content of Ca(OH)2 in the carbide slag is 70% to 80%; Preferably, the particle size of the carbide slag is 10 to 15 μm.
7. The high temperature resistant cement for cementing according to claim 1, wherein: The mass content of P2O5 in the phosphorus slag is 40% to 43%, the mass content of SiO2 is 47% to 52%, the mass content of Fe2O3 is 2% to 5%, the mass content of fluoride is 0.8% to 3%, and the mass content of Al2O3 is 0.8% to 2.5%; Preferably, the particle size of the phosphorus slag is 0.5-5 mm.
8. The high temperature resistant cement for cementing according to claim 1, wherein: The content of CaCO3 in the mussel shell powder is 90% to 96%; Preferably, the particle size of the mussel shell powder is 200-300 μm.
9. The high temperature resistant cement for cementing according to claim 1, wherein: The mass content of CaCO3 in the sugar filter mud is 55% to 70%.
10. A high temperature resistant cement slurry system for cementing, comprising the following components, in parts by weight: 100 parts of the high temperature resistant cement for cementing according to any one of claims 1 to 9, 0 to 70 parts of quartz sand, 1 to 6 parts of a suspension stabilizer, 2 to 9 parts of a fluid loss reducer, 0.5 to 1.5 parts of a dispersant, 1 to 9 parts of a retarder, 0.1 to 0.5 parts of a defoaming agent, and 40 to 100 parts of water.
11. The high temperature resistant cement slurry system for cementing according to claim 10, wherein: The particle size of the quartz sand is 50-5000 mesh, and the quartz sand includes ordinary quartz sand and / or acid-washed quartz sand.
12. The high temperature resistant cement slurry system for cementing according to claim 10, wherein: The suspension stabilizer includes an acrylamide polymer suspension stabilizer; Preferably, the suspension stabilizer comprises a polymer suspension stabilizer prepared from 2-acrylamido-2-methylpropanesulfonic acid, acrylamide, diallyldimethylammonium chloride and N-vinylpyrrolidone as monomers.
13. The high temperature resistant cement slurry system for cementing according to claim 10, wherein: The fluid loss reducer includes a 2-acrylamide-2-methylpropanesulfonic acid polymer fluid loss reducer; Preferably, the fluid loss reducer comprises a polymer fluid loss reducer prepared from 2-acrylamido-2-methylpropanesulfonic acid, N,N-dimethylacrylamide and unsaturated carboxylic acid as monomers.
14. The high temperature resistant cement slurry system for cementing according to claim 10, wherein: The dispersant includes an aldehyde-ketone polycondensate dispersant and / or a polycarboxylic acid dispersant.
15. The high temperature resistant cement slurry system for cementing according to claim 10, wherein: The retarder comprises one or a combination of hydroxy ethylene diphosphonic acid, ethylenediamine tetramethylene phosphonic acid and ethylenediamine tetramethylene phosphonate.
16. The high temperature resistant cement slurry system for cementing according to claim 10, wherein: The defoaming agent comprises one or a combination of tributyl phosphate, polyoxypropylene glycerol ether and polydimethylsiloxane.
17. A method for preparing a high temperature resistant cement slurry system for cementing according to any one of claims 10 to 16, comprising the following steps: The high temperature resistant cement for cementing, quartz sand, suspension stabilizer and dispersant are mixed uniformly according to weight parts to obtain a dry mix; the fluid loss reducer, retarder, defoamer and water are mixed uniformly according to weight parts to obtain a wet mix; at a rotation speed of 4000±200r / min, the dry mix is evenly poured into the wet mix, and after the dry mix is completely added to the wet mix, the rotation speed is adjusted to 12000±500r / min, and stirring is continued for 15-35s to obtain the high temperature resistant cement slurry system for cementing.
Citation Information
Patent Citations
High-temperature special oil well cement material and preparation method thereof
CN101906291A
High-temperature well cementation cement as well as preparation method and application thereof
CN112094060A
High-temperature-resistant well cementation cement system and preparation method thereof
CN113582605A
Oil well cement with high temperature resistance and strength decline inhibition as well as preparation method and application of oil well cement
CN113683354A
High-temperature-resistant polymerization suspension stabilizer cement paste for oil well cement and preparation method thereof
CN113736016A
